When the lights went out: impacts of the April 2025 Iberian blackout on the Portuguese National Health Service sovereignty - a reflection on national defence, health sovereignty, risk, and infrastructural dependency - Goiana-da-Silva, Francisco; Madureira-Fonseca, Daniel; Tude Graça, Duarte; Moitinho De Almeida, Maria; Cabral Pinho, Miguel; Sá, Juliana; Moreira, Rui; Cabral, Luís; Pereira, Nelson; Nunes, Alexandre Morais; Lourenço, Alexandre; Branco, Jaime; et al. (Frontiers in Public Health, 2025)
The April 2025 blackout in the Iberian Peninsula severely disrupted The Portuguese National Health Service (NHS). It led to failures for over eight hours in power supply, digital systems, telecommunications, and inter-institutional coordination. Hospitals operated on limited generator capacity, essential medical equipment was triaged, and digital health records became inaccessible. Cold storage failures endangered temperature-sensitive medicines, while emergency communications and transport systems were severely compromised. This perspective article based on first-hand experience and grey literature proposes a first rapid analyses on the blackout as through the World Health Organization’s Health Emergency and Disaster Risk Management Framework. Advocating that health care resilience must then be acknowledged as a fundamental area of national security the article calls for regulatory improvement, decentralized energy solutions, digital redundancy, and integrated command structures linking health, civil protection, and defence sectors. It offers further insights into building anticipatory health systems capable of withstanding future complex disruptions.